2019
DOI: 10.1371/journal.pone.0214525
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence for understanding concussion: Retrospective cluster analysis on the balance and vestibular diagnostic data of concussion patients

Abstract: Objectives We propose a bottom-up, machine-learning approach, for the objective vestibular and balance diagnostic data of concussion patients, to provide insight into the differences in patients’ phenotypes, independent of existing diagnoses (unsupervised learning). Methods Diagnostic data from a battery of validated balance and vestibular assessments were extracted from the database of the Swiss Concussion Center. The desired number of clusters within the patient datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 62 publications
0
15
0
1
Order By: Relevance
“…As we previously reported, Eo and Ec phybrata features were differentially predictive of clinical impairment [58], and the present NTS RF model results confirm this past work. The one published machine learning study relevant to Use Case 2 carried out a retrospective cluster analysis on the balance and vestibular diagnostic data of concussion patients using two different clustering tools (K-means and self-organizing map) [37], and demonstrated the presence of two distinct groups, one with prominent vestibular disorders and another with no clear vestibular or balance problems. However, this study did not include ROC analyses of diagnostic sensitivity, specificity, F1, or AUC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As we previously reported, Eo and Ec phybrata features were differentially predictive of clinical impairment [58], and the present NTS RF model results confirm this past work. The one published machine learning study relevant to Use Case 2 carried out a retrospective cluster analysis on the balance and vestibular diagnostic data of concussion patients using two different clustering tools (K-means and self-organizing map) [37], and demonstrated the presence of two distinct groups, one with prominent vestibular disorders and another with no clear vestibular or balance problems. However, this study did not include ROC analyses of diagnostic sensitivity, specificity, F1, or AUC.…”
Section: Discussionmentioning
confidence: 99%
“…Applications of machine learning to help automate concussion diagnoses and recovery monitoring have attracted significant research interest in recent years [30]. Data sources include structural and functional MRI [31], electroencephalography (EEG) [32][33][34][35][36], clinical scales [13,30,32,[37][38][39], balance and vestibular diagnostic data [37], gait analysis [30,40], eye tracking [41], blood biomarkers [42], analysis of head impact data [43][44][45], and a variety of wearable physiological sensors [33]. Wearable sensors are of particular interest because of their low cost, ease of use, and compatibility with remote patient monitoring.…”
Section: Machine Learning and Wearable Motion Sensors In Concussion Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Przed podjęciem badań z zastosowaniem AI w klinice otoneurologii należy przeprowadzić konsultacje ze specjalistami dziedzin (neurologii, okulistyki, fizjoterapii) w celu wybrania właściwych narzędzi i metod badawczych [26]. Jak wynika z dotychczasowych obserwacji i badań zastosowanie sztucznej inteligencji wpływa korzystnie na proces diagnostyczny w otoneurologii.…”
Section: Wnioskiunclassified
“…Recent AI work has used machine learning to predict symptom resolution following sport-related concussion (Bergeron et al, 2019 ). While another study used a clustering approach on vestibular and balance diagnostic data, and demonstrated two clinically distinct groups, patients with prominent vestibular disorders and others with no clear vestibular or balance impairment (Visscher et al, 2019 ). Specifically in consideration of the heterogeneity of concussion and noting the ways in which this complicates research efforts, Kenzie et al ( 2018 ) utilized causal loop diagramming to visualize relationships between concussion injury factors, including pathophysiology, deficits, symptom persistence and recovery trajectories.…”
Section: Introductionmentioning
confidence: 99%